Scenarios and Models to Support Global Conservation Targets. (January 2019) - Nicholson, Emily; Fulton, Elizabeth A.; Brooks, Thomas M.; Blanchard, Ryan; Leadley, Paul; Metzger, Jean Paul; Mokany, Karel; Stevenson, Simone; Wintle, Brendan A.; Woolley, Skipton N.C.; Barnes, Megan; Watson, James E.M.; et al.
Abstract : Global biodiversity targets have far-reaching implications for nature conservation worldwide. Scenarios and models hold unfulfilled promise for ensuring such targets are well founded and implemented; here, we review how they can and should inform the Aichi Targets of the Strategic Plan for Biodiversity and their reformulation. They offer two clear benefits: providing a scientific basis for the wording and quantitative elements of targets; and identifying synergies and trade-offs by accounting for interactions between targets and the actions needed to achieve them. The capacity of scenarios and models to address complexity makes them invaluable for developing meaningful targets and policy, and improving conservation outcomes. Highlights: The Strategic Plan for Biodiversity 2011–2020 commits countries to achieve specific conservation targets (the Aichi Targets). How such targets are designed and implemented has far-reaching implications for biodiversity worldwide. Scenarios and models hold great promise for ensuring that conservation targets are well founded, effectively implemented, and lead to good conservation outcomes, but are not currently being used to their full potential. In particular, scenarios and models can ensure quantitative targets are based on scientific evidence. Our review highlights information gaps, where data and models are lacking, and implementation gaps, where the theory and tools exist but have seen little use. Both gaps present opportunities for collaboration between decision-makers and researchers as the global community moves towards new sets of conservation targets beyond 2020.